1979
DOI: 10.1038/282680a0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure of a left-handed double helical DNA fragment at atomic resolution

Abstract: The DNA fragment d(CpGpCpGpCpG) crystallises as a left-handed double helical molecule with Watson-Crick base pairs and an antiparallel organisation of the sugar phosphate chains. The helix has two nucleotides in the asymmetric unit and contains twelve base pairs per turn. It differs significantly from right-handed B-DNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

45
1,089
2
9

Year Published

1981
1981
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 2,035 publications
(1,155 citation statements)
references
References 32 publications
45
1,089
2
9
Order By: Relevance
“…Netropsin increases cross-linking of angelicin (Lown & Sim, 1978), perhaps by helping stabilize the unusual conformation. (d) Finally, the discovery that d(C-G)yd(C-G), can form the novel "Z" structure (Wang et al, 1979) raises the possibility that, without gross perturbation from bound molecules, DNA itself can form stable alternative structures dependent on base sequence. Because all these experiments were done on T4 DNA, we have not excluded the possibility that one of the two putative types of cross-linking sites is characterized by the presence of glucosylated hydroxymethylcytosine near the site or by the type of glucosylation.…”
Section: Discussionmentioning
confidence: 99%
“…Netropsin increases cross-linking of angelicin (Lown & Sim, 1978), perhaps by helping stabilize the unusual conformation. (d) Finally, the discovery that d(C-G)yd(C-G), can form the novel "Z" structure (Wang et al, 1979) raises the possibility that, without gross perturbation from bound molecules, DNA itself can form stable alternative structures dependent on base sequence. Because all these experiments were done on T4 DNA, we have not excluded the possibility that one of the two putative types of cross-linking sites is characterized by the presence of glucosylated hydroxymethylcytosine near the site or by the type of glucosylation.…”
Section: Discussionmentioning
confidence: 99%
“…As already reported in the introduction to this paper, the analysis of the crystallographic data and the construction of the corresponding models ha\ e suggested to their authors [1,2] that a number of reactive sites on the bases should be more accessible in Z DNA than in its B DNA counterpart. The observation concern\ in particular atoms such as N7(G), O6(G) and CX(G) known to be the receptor sites for covalent bond formation with ;I scries of carcinogenic compounds (see e.g.…”
Section: Sitr Potrn Finand Urid a Ccessih Ili F Iesmentioning
confidence: 78%
“…structure of Z D N A indicated that certain of its base-pair atoms on its convex face are unusually exposed, the hypothesis was put forward [1,2] that if Z-DNA segments were interspersed within a B-DNA chain, these atoms could represent privileged targets for appropriate attacking species, e.g. C-8 of guanine, C8(G), could be wch a target for the carcinogen N-2-acetylaminofluorene which preferentially attacks this site.…”
Section: Camer D(c-g-c-g-a-a-t-t-c-g-c-g) Which Although Cor-mentioning
confidence: 99%
See 1 more Smart Citation
“…However, X-rays studies on crystals of alternating d(CpG)-DNA fragments and on fibers of poly(dG-dC) • poly(dG-dC) have demonstrated a left-handed double helix termed Z-DNA [1][2][3][4]. In solution, poly-(dG-dC) • poly(dG-dC) can adopt the B-or Z-form depending upon the ionic strength of the medium [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%